Early supplementation with Lactobacillus rhamnosus HN001 reduces eczema prevalence to 6 years: does it also reduce atopic sensitization?. Issue 9 (20th August 2013) - Wickens, K.; Stanley, T. V.; Mitchell, E. A.; Barthow, C.; Fitzharris, P.; Purdie, G.; Siebers, R.; Black, P. N.; Crane, J.
Summary Background The role of probiotics in prevention of allergic disease is still not clear; efficacy may depend on the timing, dose, duration, and specific probiotic used. Using a double‐blind randomized placebo‐controlled trial (Australian New Zealand Clinical Trials Registry: ACTRN12607000518460), we have shown that in a high‐risk birth cohort, maternal supplementation from 35 weeks gestation until 6 months if breastfeeding and infant supplementation from birth until 2 years with Lactobacillus rhamnosus HN001 (HN001) (6 × 109 cfu/day) halved the cumulative prevalence of eczema at 2 and 4 years. Bifidobacterium animalis subsp lactis HN019 (HN019) (9 × 109 cfu/day) had no significant effect. Objective To determine whether differences in effects of HN001 and HN019 on eczema persist to age 6 years, and to investigate effects on sensitization. Methods Standard procedures were used to assess eczema (The UK Working Party's Criteria), eczema severity (SCORAD), atopic sensitization [skin prick tests (SPT), total and specific IgE] and standard questions used for asthma, wheeze, and rhinoconjunctivitis. Results HN001 was associated with significantly lower cumulative prevalence of eczema (HR = 0.56, 95% CI 0.39–0.80), SCORAD ≥ 10 (HR = 0.69, 0.49–0.98) and SPT sensitization (HR = 0.69, 95% CI 0.48–0.99). The point prevalence of eczema (RR = 0.66, 95% CI 0.44–1.00), SCORAD ≥ 10 (RR = 0.62, 95% CI 0.38–1.01) and SPT sensitization (RR = 0.72, 95% CI 0.53–1.00) were also reduced among children taking HN001. HN019 had no significant effect on any outcome. Conclusion and Clinical Relevance This study provides evidence for the efficacy of the probiotic L. rhamnosus HN001 in preventing the development of eczema and possibly also atopic sensitization in high risk infants to age 6 years. The absence of a similar effect for HN019 indicates that benefits may be species specific.